Poemas "Vilanos", "Utopía de Libertad" y "Que en la oscuridad ocurran cosas" - Huerta Ortiz, José (Milenaria, Ciencia y arte, 2021)
Poemas Vilanos. Utopía de Libertad. Que en la oscuridad ocurran cosas.